Effective teaching and learning through digital course content development: a uitm model / Mohd Nor Mamat … [et al.] - Mamat, Mohd Nor; Hasrol Jono, Mohd Nor Hajar; Abdul Aziz, Azlan; Za'ba, Nurmaisara (Penerbit UiTM (UiTM Press), 2009)
Electronic Learning (e-Learning) is not new in today’s education system. The success of eLearning application depends not only on the info structure and the Learning Management System (LMS) but also on the content fulfillment to be uploaded and downloaded. Dependency on the system and the info structure does not cater to the successful teaching and learning process without the distributed and accessed information or the module. The lackluster of the content fulfillment in the smart school project serves as a reminder that a proper and thoroughly thought out plan on training and digital content development must not be verlooked. In the realm of tertiary education, the requirement for online learning is of great relevance in line with the society needs to have tertiary education due to the constraint of campus capacity. UiTM is a unique university with 12 branch campuses and over 150,000 students around Malaysia. The question is actually to gauge on the content development for huge number of users, considering user-friendliness, efficiency, effectiveness and meet the humanistic aspects at the same time.